Nonstandard Finite Difference Scheme for a Computer Virus Model - Kocabıyık, Mehmet; Özdoğan, Nihal; Ongun, Mevlüde Yakıt (Bursa Teknik Üniversitesi, 2020)
This study introduces us to a new model developed for computer viruses. The model is presented to remove the protective restriction on the total number of computers connected to the Internet. This model is nonlinear differential equation system. Therefore, finding analytical solutions is very difficult. This means that we have to apply numerical methods in order to find the solution. The behavior of numerical solution has been investigated for the discretized system. By using Nonstandard Finite Difference Scheme (NSFD), it is aimed to preserve both the positivity of the solutions for positive initial points and the local asymptotic stability of the equilibrium point.
TUBITAK 2211
Keywords: Engineering; Mühendislik